Studi Risiko Penggunaan Kayu Bakar Terhadap Kejadian Bayi Berat Lahir Rendah - Widaryana, I Dewa Made; Setiani, Onny; Adi, M. Sakundarno (Jurnal Kesehatan Lingkungan Indonesia, 2003)
ABSRACT Background : Low birth weight incidence in Central Java is still high (1.2 %) compare to birth life. Faktor that may cause low birth weight intrinsic factors (i.e. mothers nutrition, anemia, etc.), and extrinsic factors i.e. physical factor, chemist, and social economic. One of chemical  factor was carbon monoxide exposure from wood smoke. Fire wood consumption in Central Java is still high ( Rp.3.093, - per capita)  compare to  gasoline consumption  (Rp.1.093/per capita) and Liquid Petroleum Gas (Rp.43, - per capita). The main objective  of this research is to  measure the  risk of the using of  fire wood to low birth weight incidence. Methods :This research a case control study, that used 84 low birth weight infant for case, compare to 84 non low birth weight infant  for control and infant mothers as respondents. Results :The research  show that the using of fire wood has OR=1.493  95%CI= 0.801-2.783, period time wood fuel before pregnant (in year) result OR=1.118;95%CI = 0.581-2.151, exposure duration  before pregnant (hours/day) has OR=1.402 ;95% CI= 0.761-2.582, exposure duration in pregnant (in trimester) has OR=1.538;95%CI=  0.837 – 2.826, exposure duration in pregnant (hours/day) result OR=1.471 ;95% CI=0.799-2.708. Conclusion : There is no significant influence of the using of fire wood to low birth weight in Semarang District. Supposed for another researchers, to research in stage II (ambient) and stage III (biomarker), because this research is only in stage I (sources) and stage IV (impact). Key Words : Fire woodl, Low Birth Weight, Semarang  District, 2002